Development and Determinants of Islamic Capital Market Performance In Indonesia: A Systematic Literature Review Period 2019-2025 - Dicky Aditya; Intan Kurnia Ningsih (Universitas Darunnajah, 2025)
Despite the significant growth of Indonesia's Islamic capital market, there remains a lack of comprehensive synthesis regarding research developments, performance determinants, and methodological approaches used in studying this market during recent years. This study aims to systematically review the development and determinants of Islamic capital market performance in Indonesia during 2019-2025. Using the PRISMA 2020 framework, we analyzed 100 empirical articles from Indonesian academic databases focusing on research trends, determinant factors, and empirical models. The results show a significant increase in publications, especially during the COVID-19 pandemic period (2021-2023). Macroeconomic factors (inflation, exchange rates, BI rate) and market-specific factors (liquidity, capitalization, volatility) are the main determinants consistently found across studies. GARCH family models and ARDL are the most frequently used methodological approaches. The findings indicate that the Indonesian Islamic capital market is influenced by both conventional economic factors and Sharia-specific screening mechanisms. This study contributes to the literature by providing a comprehensive synthesis of Islamic capital market performance research in Indonesia, identifying consistent determinants, evaluating methodological patterns, and highlighting research gaps for future studies in market microstructure, investor behavior, spillover effects, and ESG integration.